Development of a Minimally Invasive Serum Test for Liver Cirrhosis - Padma, Somrita; Ghosh, Rishila; Barman, Manabendu; Bhatia, Yeshika; Duseja, Ajay; Dutta, Sankhadeep; Panda, Chinmoy Kumar; Ahmed, Hafiz; Chatterjee, Bishnu Pada (British Journal of Healthcare and Medical Research, 2026)
Phosphorylation is one of the most important post-translational modifications of proteins. Although cellular phosphorylation has been studied extensively, research on phosphoproteomes in patients’ serum with hepatitis is limited. Serum phosphoproteins and phosphopeptides could be considered important disease biomarkers, as they play roles in cellular function. We previously reported higher serum levels of the phosphoZinc finger (pZNF) protein in patients with liver disease, including chronic hepatitis B (CHB), CHB-induced liver cirrhosis (CHB-LC), and CHB-induced hepatocellular carcinoma (CHB-HCC). To develop a minimally invasive pZNF protein-based diagnostic test for liver diseases (CHB, CHB-LC, HCC) from serum, we first synthesized a pZNF peptide based on our MALDI-ToF-MS peptide analysis data and developed polyclonal antibodies specific to pZNF. Using the pZNF-specific antibodies, an optimized Enzyme-Linked Immunosorbent Assay (ELISA) was then developed to screen sera from CHB (n=20), CHB-LC (n=17), CHB-HCC (n=20), and healthy volunteers (n=20). Results from the optimized ELISA test showed that sera from patients with liver diseases could be reliably detected, whereas those from healthy individuals could not (87.7% sensitivity and 76.9% specificity at a 300 cut-off; 82.6% sensitivity and 90.9% specificity at a 400 cut-off). Interestingly, the CHB-LC cohort stood out from the rest cohorts as it showed the highest expression of pZNF protein. At an 800-cut-off value, 17 of 17 CHB-LC samples were detected (above the cut-off), yielding a sensitivity of 100%. At the same cut-off value (800), only 2 of 60 samples were false positives, yielding a specificity of 96.8%. The two positive samples were from the CHB cohort, none from the HV cohort. Overall, we successfully developed a serum test (minimally invasive) that could detect CHB and CHB-induced liver diseases, particularly CHB-LC, with 100% sensitivity and nearly 100% specificity.